2010
DOI: 10.1002/hrm.20353
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and retention in foreign firms in India: A resource‐based view

Abstract: Foreign fi rms in India currently face two major challenges in human resource management (HRM): personnel recruitment and retention. For this study, we adapted the resource-based view (RBV) of the fi rm and tested which recruitment and retention practices positively impact the number of qualifi ed applicants and the attrition rate in a sample of 80 North-Western European fi rms. Our fi ndings suggest that a close relationship exists between using recruitment and retention practices shaped according to the RBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 74 publications
1
44
0
1
Order By: Relevance
“…While the per The International Journal of Human Resource Management 1753 capita income in the latter is still considerably lower than in developed countries, China and India have caught up in recent years. In particular, the wage level in the corporate sector has increased significantly (Holtbrügge et al 2010;Yang, Chen and Monarch 2010;International Labour Organization 2012). Thus, employees in these countries may perceive their basic needs as satisfied and the consideration of environmental issues as more relevant than before.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While the per The International Journal of Human Resource Management 1753 capita income in the latter is still considerably lower than in developed countries, China and India have caught up in recent years. In particular, the wage level in the corporate sector has increased significantly (Holtbrügge et al 2010;Yang, Chen and Monarch 2010;International Labour Organization 2012). Thus, employees in these countries may perceive their basic needs as satisfied and the consideration of environmental issues as more relevant than before.…”
Section: Discussionmentioning
confidence: 98%
“…On the contrary, the environmental reputation of a company in emerging economies, which are characterized by lower salary levels, may be less relevant for the decisions of employees to stay in that company (Child and Tsai 2005;Lo et al 2008). Here, the commitment of employees may be more determined by financial incentives and career perspectives (Holtbrügge et al 2010). Hence, we propose:…”
Section: Environmental Reputation and Employee Commitment In Developementioning
confidence: 97%
See 1 more Smart Citation
“…This opinion is promoted by Holtbrugge, Friedmann, & Puck (2010) in their research that they found that internal recruitment positively affects the quality of job applicants in European companies residing in India. Referring to the goal-setting theory of Locke which says that more difficult and specific goals will improve one's performance (in Robin & Judge, 2013).…”
Section: Looking For Superior Student Candidatementioning
confidence: 99%
“…It is important that employers endeavour to retain highpotential employees and replace the low performers with new employees with diverse skills and strong ability (Holtbrugge, Friedman & Puck, 2010). Turnover can be considered positive if talented employees are retained while lower performers leave the organisation (Hausknecht et al, 2009).…”
Section: Factors That Impact Retention Of High-potential Employeesmentioning
confidence: 99%